Potential of Mycobacterium tuberculosis Type II NADH-Dehydrogenase in Antitubercular Drug Discovery - Saha P.; Kumar M.; Sharma D.K. (My University, 2025)
The type II NADH-dehydrogenase enzyme in Mycobacterium tuberculosis plays a critical role in the efficient functioning of the oxidative phosphorylation pathway. It acts as the entry point for electrons in the electron transport chain, which is essential for fulfilling the energy requirements of both replicating and nonreplicating mycobacterial species. Due to the absence of the type II NADH-dehydrogenase enzyme in mammalian mitochondria, targeting the type II NADH-dehydrogenase enzyme for antitubercular drug discovery could be a vigilant approach. Utilizing type II NADH-dehydrogenase inhibitors in antitubercular therapy led to bactericidal response, even in monotherapy. However, the absence of the cryo-EM structure of Mycobacterium tuberculosis type II NADH-dehydrogenase has constrained drug discovery efforts to rely on high-throughput screening methods, limiting the use of structure-based drug discovery. Here, we have delineated the literature-reported Mycobacterium tuberculosis type II NADH-dehydrogenase inhibitors and the rationale behind selecting this specific enzyme for antitubercular drug discovery, along with shedding light on the architecture of the enzyme structure and functionality. The gap in the current research and future research direction for TB treatment have been addressed. © 2025 American Chemical Society.